2022
DOI: 10.2196/34577
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Retirement Communities: Scoping Review

Abstract: Background As Canada’s population ages, there is a need to explore community-based solutions to support older adults. Naturally occurring retirement communities (NORCs), defined in 1986 as buildings or areas not specifically designed for, but which attract, older adults and associated NORC supportive service programs (NORC-SSPs) have been described as potential resources to support aging in place. Though the body of literature on NORCs has been growing since the 1980s, no synthesis of this work has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
(259 reference statements)
0
5
0
Order By: Relevance
“…When supportive home care and community support are embedded into these environments, older adults are able to remain living in the community as long as possible and avoid or delay the transition to an LTC facility. Similarly, innovative architecture (signage, color, space, light, and views of nature) in LTC facilities can better enable social interactions, physical activity, and time spent in nature [ 28 , 140 , 159 ], contributing to mental wellness and overall life satisfaction [ 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…When supportive home care and community support are embedded into these environments, older adults are able to remain living in the community as long as possible and avoid or delay the transition to an LTC facility. Similarly, innovative architecture (signage, color, space, light, and views of nature) in LTC facilities can better enable social interactions, physical activity, and time spent in nature [ 28 , 140 , 159 ], contributing to mental wellness and overall life satisfaction [ 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study found that the most discussed article was " social environment" and that NORCs are a perfect model for healthy aging. Parniak et al , ( 2022) summarized the current research on NORCs with 64 articles and described how NORCs can support aging in place for older adults. The study suggested that NORC-SSPs have the potential to be an alternative model for supporting aging in place.…”
Section: Abstract Co-occurrence Analysismentioning
confidence: 99%
“…Jiaxuan et al ( 2022) provided an overview of NORC and found that the social environment provides the necessary moral support and material motivation for older adults to live actively in NORC. Parniak et al ( 2022) conducted a scoping review of NORC and summarized the current state of the relevant literature. Secondly, NORC Supportive Service Programs (NORC-SSP) were studied (Greenfield, 2014).…”
Section: Research Trendsmentioning
confidence: 99%
“…New concepts such as "aging in community" (AIC) emphasise and expand the understanding of place beyond the home to include the community and neighbourhood levels (Thomas & Blanchard, 2009). Previous research on models supporting AIC has explored community-dwelling facilities, retirement villages, the village model, and naturally occurring retirement communities (Grant, 2007;Greenfield et al, 2013;McDonough & Davitt, 2011;Parniak et al, 2022;Scharlach et al, 2012). In this study, we focus on a local social innovation, the Social Hub model, which is a local innovation developed to support community building at a neighbourhood level.…”
Section: Introductionmentioning
confidence: 99%